Menggagas Hospitalitas Pentakostal: Membaca Ulang Kisah Para Rasul 2:44-47 di Masa Pandemi - Johannis Siahaya; Harls Evan R. Siahaan (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Abstract. The Covid-19 pandemic demands serious handling and response, not only at the level of regulation which resulted in a policy of breaking the chain of spreading the deadly virus in the social order, but also stimulating the church's attitude in alleviating the suffering of the people affected. This article is a study of Pentecostal reflective on the text of Acts 2:44-47, which was aimed to produce a theological attitude about caring for others in order to alleviate the suffering of the people, to the wider community outside the church, who are affected by the pandemic. This research was conducted by a qualitative approach with descriptive, analysis-interpretative, and comparative-argumentation methods, to gain new understanding of the text being studied. In conclusion, the rereading of Acts 2:47 proposed the hospitality of the Pentascostals, which not only show Christian kindness, but also a liturgical praxis.Abstrak. Peristiwa pandemi Covid-19 menuntut penanganan dan respons yang serius, bukan hanya pada tataran regulasi yang membuahkan kebijakan memutus mata rantai penyebaran virus mematikan tersebut pada tatanan sosial, namun juga menstimulasi sikap gereja dalam meringankan penderitaan umat yang terdampak. Artikel ini merupakan sebuah kajian reflektif kaum Pentakostal atas teks Kisah Para Rasul 2:44-47, yang bertujuan untuk menghasilkan sikap teologis tentang kepedulian terhadap sesama dalam rangka meringankan penderitaan umat, hingga masyarakat luas di luar gereja, yang terdampak pandemi. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, analisis-interpretatif, serta argumentasi-komparatif, untuk mendapatkan pemahaman baru dari teks yang dikaji. Kesimpulannya, pembacaan ulang Kisah Para Rasul 2:44-47 menggagas sikap hospitalitas kaum Pentaskostal, yang bukan hanya sekadar menunjukkan kebaikan Kristen, namun juga tindakan liturgis.